Effect of a protein and energy dense n-3 fatty acid enriched oral supplement on loss of weight and lean tissue in cancer cachexia: a randomised double blind trial. Issue 10 (11th September 2003) - Fearon, K C H; von Meyenfeldt, M F; Moses, A G W; van Geenen, R; Roy, A; Gouma, D J; Giacosa, A; Van Gossum, A; Bauer, J; Barber, M D; Aaronson, N K; Voss, A C; et al.
Abstract : Aim: N-3 fatty acids, especially eicosapentaenoic acid (EPA), may possess anticachectic properties. This trial compared a protein and energy dense supplement enriched with n-3 fatty acids and antioxidants (experimental: E) with an isocaloric isonitrogenous control supplement (C) for their effects on weight, lean body mass (LBM), dietary intake, and quality of life in cachectic patients with advanced pancreatic cancer. Methods: A total of 200 patients (95 E; 105 C) were randomised to consume two cans/day of the E or C supplement (480 ml, 620 kcal, 32 g protein ± 2.2 g EPA) for eight weeks in a multicentre, randomised, double blind trial. Results: At enrolment, patients' mean rate of weight loss was 3.3 kg/month. Intake of the supplements (E or C) was below the recommended dose (2 cans/day) and averaged 1.4 cans/day. Over eight weeks, patients in both groups stopped losing weight (Δ weight E: −0.25 kg/month versus C: −0.37 kg/month; p = 0.74) and LBM (Δ LBM E: +0.27 kg/month versus C: +0.12 kg/month; p = 0.88) to an equal degree (change from baseline E and C, p<0.001). In view of evident non-compliance in both E and C groups, correlation analyses were undertaken to examine for potential dose-response relationships. E patients demonstrated significant correlations between their supplement intake and weight gain ( r = 0.50, p<0.001) and increase in LBM ( r = 0.33, p = 0.036). Such correlations were not statistically significant in C patients. The relationship of supplement intake with change in LBM was significantly different between E and C patients (p = 0.043). Increased plasma EPA levels in the E group were associated with weight and LBM gain ( r = 0.50, p<0.001; r = 0.51, p = 0.001). Weight gain was associated with improved quality of life (p<0.01) only in the E group. Conclusion: Intention to treat group comparisons indicated that at the mean dose taken, enrichment with n-3 fatty acids did not provide a therapeutic advantage and that both supplements were equally effective in arresting weight loss. Post hoc dose-response analysis suggests that if taken in sufficient quantity, only the n-3 fatty acid enriched energy and protein dense supplement results in net gain of weight, lean tissue, and improved quality of life. Further trials are required to examine the potential role of n-3 enriched supplements in the treatment of cancer cachexia.